A Study on Stereoselective Glycosylations via Sulfonium Ion Intermediates. Issue 27 (26th August 2016) - Mensink, Rens A.; Elferink, Hidde; White, Paul B.; Pers, Nathalie; Rutjes, Floris P. J. T.; Boltje, Thomas J.
Abstract : The stereoselective synthesis of 1, 2‐ cis ‐linkages can be achieved by an Sn2‐like displacement of glycosylation intermediates such as glycosyl triflates and sulfonium ions, provided that they display the right combination of stability and reactivity. Herein, we report the use of an achiral auxiliary that can impose neighboring group participation to afford glycosyl sulfonium ions, aided by the Thorpe–Ingold effect. We investigated the glycosylation properties of the sulfonium ions and used variable temperature NMR (VT‐NMR) studies to investigate their role in the glycosylation mechanism. The influence of the structure of the auxiliary, the protecting groups and stereochemistry of the glycosyl donor were investigated and led to the identification of a highly α‐selective galactose donor. Abstract : New C‐2 auxiliaries and mechanistic insights into stereoselective glycosylation reactions involving sulfonium ion intermediates are disclosed